PENGARUH BIMBINGAN BELAJAR ORANG TUA TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SDN SEKECAMATAN PURING TAHUN AJARAN 2020/2021 - Diah Palupi; Ngatman Ngatman; Tri Saptuti Susiani (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2021)
AbstractThis study aims to: 1) find out whether there is a positive influence of parental tutoring on the science learning outcomes of fourth grade elementary school students in Puring Sub-district in the academic year of 2020/2021, 2) find out the contribution of parental tutoring on the science learning outcomes of fourth grade elementary school students in Puring Sub-district in the academic year of 2020/2021. This research belongs to quantitative research using simple linear regression method. The population of this research is all fourth grade students of the elementary school in Puring Sub-district in the academic year of 2020/2021, consisting of 875 students. The sample of this study amounted to 293 fourth grade elementary school students in twelve public elementary schools throughout Puring Sub-district in the academic year of 2020/2021 who were randomly selected with probability sampling technique. The researcher uses questionnaires and learning outcomes tests to collect the data. The results showed that: (1) there was a positive and significant effect of parental tutoring on the science learning outcomes of fourth grade elementary school students in Puring Sub-district in the academic year of 2020/2021 with a regression of 0.255. (2) The contribution of parental tutoring to the science learning outcomes of fourth grade elementary school students in Puring Sub-district in the academic year of 2020/2021 is 25.5% and the remaining 74.5% is influenced by other factors such as interests, talents, intelligence, study habits, perseverance, family environment, school, and community environment.AbstrakPenelitian ini bertujuan untuk: 1) mengetahui ada tidaknya pengaruh positif bimbingan belajar orang tua terhadap hasil belajar IPA siswa kelas IV SDN se-Kecamatan Puring tahun ajaran 2020/2021, 2) mengetahui besarnya sumbangan bimbingan belajar orang tua terhadap hasil belajar IPA siswa kelas IV SDN se-Kecamatan Puring tahun ajaran 2020/2021. Penelitian ini merupakan penelitian kuantitatif dengan metode regresi linier sederhana. Populasi penelitian ini adalah seluruh siswa kelas IV SDN se-Kecamatan Puring tahun ajaran 2020/2021 yang berjumlah 875 siswa. Sampel pada penelitian ini berjumlah 293 siswa kelas IV SD di dua belas SDN se-Kecamatan Puring tahun ajaran 2020/2021 yang dipilih secara acak dengan teknik probability sampling. Teknik pengumpulan data menggunakan angket dan tes hasil belajar. Hasil penelitian menunjukkan bahwa: (1) terdapat pengaruh positif dan signifikan bimbingan belajar orang tua terhadap hasil belajar IPA siswa kelas IV SDN se-Kecamatan Puring tahun ajaran 2020/2021 dengan regresi sebesar 0,255. (2) sumbangan bimbingan belajar orang tua terhadap hasil belajar IPA siswa kelas IV SDN se-Kecamatan Puring tahun ajaran 2020/2021 sebesar 25,5% dan sisanya 74,5% dipengaruhi oleh faktor lain seperti minat, bakat, kecerdasan, kebiasaan belajar, ketekunan, lingkungan keluarga, sekolah, dan lingkungan masyarakat